Comparing regional effects of climate policies to promote non-fossil fuels in China. (15th December 2017) - Li, Aijun; Peng, Dan; Wang, Daoping; Yao, Xin
Abstract: China is a large developing and transitional economy with substantial regional gaps and high trade openness. However, to our knowledge, the existing studies do not capture the regional impacts of climate policies promoting non-fossil fuels in China. To fill this gap, this study develops a new multi-country multi-region computable general equilibrium (CGE) model, with detailed energy disaggregation. It compares the regional effects of alternative climate policies and discusses how to improve the performance. The main findings are as follows. Firstly, climate policies promoting low-carbon energy are not neutral, since different regions, sectors or countries are affected disproportionally. In this regard, this study provides detailed information about regional variations and effects, which is quite useful and important for policy makers in local governments. Secondly, there are sharp differences in effects between energy subsidy and carbon tax. These two policies produce differentiated effects on renewable energy, outputs, fiscal spending and cross-border externalities. Finally, goal settings are important for designing effective climate policies. There are considerable differences between absolute-emission-reduction goals and intensity-based emission goals. Looking ahead, the Chinese government should develop well-designed policy mix to promote non-fossil fuels. Highlights: This study develops a new multi-country multi-region CGE model. It compares regional effects of climate policies promoting renewable energy. These policies are not neutral across regions, sectors or countries. Detailed information is provided regarding regional variations and effects.